Voltammetric determination of all DNA nucleotides - Brett, A. M. Oliveira (2004)
The voltammetric oxidation of all deoxyribonucleic acid (DNA) monophosphate nucleotides is investigated for the first time over a wide pH range by differential pulse voltammetry with a glassy carbon electrode. Experimental conditions such as the electrode size, supporting electrolyte composition, and pH were optimized to obtain the best peak potential separation and higher currents. This enabled the simultaneous voltammetric determination of all four DNA bases in equimolar mixtures and detection limits in the nanomolar range at physiological pH. It was also possible to detect for the first time the oxidation of each of the purine and pyrimidine nucleotides free in solution or as monomers in single-stranded DNA.